The Effects of Two Different Exercise Programs on the Ultrastructural Features of the Sciatic Nerve and Soleus Muscle After Sciatic Crush. Issue 9 (12th May 2017) - Bonetti, Leandro Viçosa; Malysz, Taís; Ilha, Jocemar; Barbosa, Silvia; Achaval, Matilde; Faccioni‐Heuser, Maria Cristina
ABSTRACT: Peripheral nerve injuries constitute a significant medical problem and the recovery is critically dependent on post‐injury treatment. In this study, following sciatic nerve crush, we investigated the effects of a 4‐week endurance training program (ET) and balance and coordination training program (BCT) on the ultrastructural features of the sciatic nerve and soleus muscle. The animals were randomly divided into Sham, non‐trained (NT), ET, and BCT groups each of which included three animals. Ultra‐thin cross and longitudinal sections (70–85 nm) were digitized and analyzed comparatively. The electron micrographic analysis of the sciatic nerve showed similar organelles features in the injury groups (myelin debris and swelling mitochondria). Nonetheless, the ET group presented better ultrastructural features as demonstrated by the greater predominance of rounded fibers and more defined organization in the myelinated axon bundles. In the soleus muscle's analyses, the injured groups demonstrated similar organelles' features (nucleus contained highly heterochromatic nuclei and smaller mitochondria). However, ET and BCT groups showed apparently enlarged myofibril cross‐sectional areas and less collagen around muscle fibers, although, the ET group displayed reduced intermyofibrillar spaces and more closely aligned myofilaments when compared with the BCT group. Based on electron micrographic analysis, our findings suggest the presence of ultrastructural differences between the Sham, NT, and the trained groups. Therefore, exercise type seems to be responsible for producing some different positive features in the trained groups, while ET seems to have a more pronounced influence on the ultrastructural features of the sciatic nerve and the soleus muscle after a crush injury. Anat Rec, 300:1654–1661, 2017. © 2017 Wiley Periodicals, Inc.